0644 Bright Light Therapy To Reduce Fatigue And Improve Sleep Quality In Lung Cancer Survivors. (27th April 2018) - Weiss, C; Dickerson, S; Dubocovich, M L; Dean, G E
Abstract: Introduction: Lung cancer survivors (LCS) have the worse sleep quality among cancer survivors. Bright light therapy (BLT) has been used to treat fatigue, sleep and circadian rhythm disorders (CAR) in cancer populations, but not for LCS. This study tested a new approach using one-week of morning BLT intervention to treat sleep disturbances in lung cancer survivors. Methods: An RCT design was used to explore the effects of morning BLT on fatigue, sleep quality and CAR in LCS. Fourteen non-small cell lung cancer survivors, stage I-III were randomly assigned to experimental (green-blue) and attention control (red-yellow) light groups. Exclusion criteria included macular degeneration, glaucoma, bipolar disorder, seizure disorder or psychiatric conditions. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI). Daily fatigue measures were incorporated in the Sleep Diary. Data collection encompassed two-week of baseline, one-week intervention, two-weeks posttest. Sleep diary and actigraphy data were collected throughout the 5-week study. Data were analyzed using t-test, ANOVA, and non-parametric analysis as appropriate. Results: Predominance of female (83.3%), older (mean age 68.5) sample, with morning chronotype (42.9%), clinically significant insomnia (42.9%) and moderate to severe fatigue (57.2%). Repeated measures ANOVA with sphericity assumed showed a main effect of time over fatigue (F= 5.303, 1.672, p = 0.002). Decreased fatigue levels were observed in experimental group at week 3 (score= 1.65) and remained low during week 4 (score= 1.90) and 5 (score = 1.77). Fatigue levels did not significantly change with time in the control group. Significant improvement in sleep quality (p<0.001). Mean PSQI global scores for experimental group were 9.73 ± 3.58 at pre-test and 6.29 ± 1.25 at posttest. Meanwhile, the control group had 9.8 ± 2.58 at pre-test and 8.80 ± 2.28 at posttest. Conclusion: One week of morning BLT was sufficient to reduce fatigue and improve sleep quality. Noticeable improvement in fatigue on the experimental group during the intervention and sustained lower fatigue levels postintervention. Despite the improvement in subjective sleep quality, persistent mean PSQI global scores above 5 indicated that LCS are poor sleepers. Support (If Any): Oncology Nursing Society.